2016
DOI: 10.1177/1934578x1601100920
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Monoamine Oxidases and Cholinesterases Inhibitory Effects, as well as UPLC-DAD-MS Chemical Profile of Alkaloid Fractions Obtained from Species of the Palicoureeae Tribe

Abstract: In the present study, the effects were evaluated of alkaloid fractions (AFs) from Psychotria species and correlated genera, Palicourea and Rudgea, on monoamine oxidases (MAOs) and cholinesterases (ChEs). By HPLC-DAD and UPLC-DAD-MS analyses, indole alkaloids (IA) were detected in all AFs. For the Psychotria and Palicourea species, these IA corresponded to tetrahydro-β-carboline alkaloids (THβCA). On the other hand, pyrrolidinoindoline core compounds were observed for Rudgea species. Regarding their pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…acetylcholinesterase (AChE), butyrylcholinesterase (BChE), monoamine oxidase A (MAO-A), MAO-B, and catechol-O-methyltransferase (COMT) has been demonstrated. [4][5][6][7][8][9][10][11][12][13] In this sense, Psychotria is considered as an important source of active compounds…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…acetylcholinesterase (AChE), butyrylcholinesterase (BChE), monoamine oxidase A (MAO-A), MAO-B, and catechol-O-methyltransferase (COMT) has been demonstrated. [4][5][6][7][8][9][10][11][12][13] In this sense, Psychotria is considered as an important source of active compounds…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that the alkaloid fraction obtained from the leaves of P. nemorosa significantly inhibited BChE and MAO-A activities. 11 Multivariate calibration techniques, such as Partial Least Squares (PLS) and Orthogonal Projections to Latent Structures (O-PLS), were used to indicate four active peaks, correlating chemical and pharmacological data. 10 However, at that time, it was not possible neither to isolate nor to determine their chemical structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation